MENINGKATKAN KEMAMPUAN KOORDINASI GERAK MATA DAN TANGAN MELALUI PERMAINAN BOWLING ADAPTIF PADA ANAK ADHD ATTENTION DEFICIT HYPERACTIVE DISORDER - Amirul Amin M (Jurnal Penelitian Pendidikan Khusus, 2012)
Improving the Motion Eye and Hand Coordination Through Adaptive Bowling Games in Children Attention Deficit Disorder Hyperaktive in SLB Amal Bhakti Sicincin (Single Subject Research) SLB D/1C class Amal Bhakti Sicincin). Thesis PLB FIP Padang State University. This approach use experimental approach in the form of Single Subject Research (SSR) design with A - B subjects of this study were children with ADHD D/1C class. This assessment is consistent and count the ability to coordinate eye and hand movements that can be done by children. These results indicate that the ability of children Attention Deficit Hyperactivity Disorder bernisial ZA in eye movement and hand coordination improved, data on baseline conditions showed 16.6%, 16.6%, 33.3%, 33.3%, 33.3 %, initially in the baseline condition the researchers did five times only able to take observations of children and do not throw that direction. data on the condition of intervention, namely 28.5%, 28.5%, 42.8%, 71.4%, 71 , 4%, 100%, 100%, in the intervention condition seven times, which is the ability of children continues to rise initially only be able to take and make the throw, until the child can and do throw manyusun targeted. Thus the problem formulation presented proved that adaptive bowling games can improve eye-hand motor coordination for children Attention Deficit Hyperactivity Disorder in SLB Amal Bhakti Sicincin. Then the researchers suggest the teacher to use adaptive bowling game in improving eye-hand motor coordination of children.